2011
DOI: 10.1096/fj.11-186650
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral deficit, oxidative stress, and mitochondrial dysfunction precede tau pathology in P301S transgenic mice

Abstract: Abnormal tau accumulation can lead to the development of neurodegenerative diseases. P301S mice overexpress the human tau mutated gene, resulting in tau hyperphosphorylation and tangle formation. Mice also develop synaptic deficits and microglial activation prior to any neurodegeneration and tangles. Oxidative stress can also affect tauopathy. We studied the role of oxidative stress in relationship to behavioral abnormalities and disease progression in P301S mice at 2, 7, and 10 mo of age. At 7 mo of age, P301… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 41 publications
8
83
0
Order By: Relevance
“…OS is a pivotal cellular response to the damage caused by tau toxicity, and the vicious interaction between these two causative events promotes AD progression [38] . Studies have identified OS as an early marker of tauopathy since OS and mitochondrial dysfunction are detected prior to tau hyperphosphorylation and NFT accumulation in tau P301S transgenic mice, which show tau hyperphosphorylation and tangle formation in 3 months [39] . On the one hand, OS amplifies tauinduced neurotoxicity by induction of apoptosis and dysregulation of cell energy metabolism and promotes tau hyperphosphorylation and aggregation [38] .…”
Section: Discussionmentioning
confidence: 99%
“…OS is a pivotal cellular response to the damage caused by tau toxicity, and the vicious interaction between these two causative events promotes AD progression [38] . Studies have identified OS as an early marker of tauopathy since OS and mitochondrial dysfunction are detected prior to tau hyperphosphorylation and NFT accumulation in tau P301S transgenic mice, which show tau hyperphosphorylation and tangle formation in 3 months [39] . On the one hand, OS amplifies tauinduced neurotoxicity by induction of apoptosis and dysregulation of cell energy metabolism and promotes tau hyperphosphorylation and aggregation [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The functional analysis of proteomics finds mitochondrial dysfunction together with reduced NADH-ubiquinone oxidoreductase activity impairs mitochondrial oxidative phosphorylation and ATP synthesis [84][85][86] . Accordingly, coenzyme Q10 (CoQ10), an antioxidant and key component of the electron transport chain, signifi cantly enhances complex I activity and reduces lipid peroxidation, and consequently, signifi cantly improves survival and the behavioral defi cits in P301S mice [87] .…”
Section: Hyperphosphorylated Taumentioning
confidence: 99%
“…Several lines of evidence support that NO impairs mitochondrial/cellular respiration and other functions by inhibiting the activities of several key enzymes, particularly cytochrome c oxidase, and thereby causing ATP depletion [46]. In cultured neuroblastoma cells, overexpression of tau results in mitochondria with decreased ATP levels and increased susceptibility to oxidative stress [47]. Furthermore, the activity and composition of mitochondrial enzymes are disrupted in the mouse model of tauopathy [48].…”
Section: Mitochondria As a Regulator Of Apoptosis And Oxidative Stressmentioning
confidence: 99%